Autobiographical memory deficits in remitted patients with bipolar disorder I: The effect of impaired memory retrieval. (August 2019) - Bozikas, Vasilis P.; Nazlidou, Elena I.; Parlapani, Eleni; Alexiadou, Amalia; Skemperi, Eleni; Dandi, Eugenia; Bargiota, Stavroula I.; Floros, Georgios; Garyfallos, Georgios
Highlights: AM involves recollection of personal information associated with one's past life. Autobiographical memory has not been studied extensively in BD. BD patients showed deficits in recalling personal episodic memories and facts. Deficits in AM were independent of patients' lower verbal memory performance. Abstract: Autobiographical memory (AM) has been studied extensively in different psychiatric disorders. However, less is known about AM in bipolar disorder (BD). Aim of the present study was to investigate BD patients' ability to recall episodic and semantic autobiographical memories after controlling for the effect of other possible neurocognitive deficits. Participants included 30 clinically remitted outpatients with BD type I and 30 healthy controls, matched for age, gender and educational level. Autobiographical memory was examined by the Questionnaire of Autobiographical Memory. Premorbid intellectual functioning, verbal memory, verbal fluency, attention and working memory were also assessed. Bipolar patients were impaired in both episodic and semantic AM, compared with healthy individuals. Deficits involved recall of memories from childhood-adolescence, early adulthood and recent life. Additionally, patients were impaired in verbal memory compared with controls. Differences between study groups in both episodic and semantic AM remained significant even after controlling for the effect of verbal memory deficits. Remitted BD-I patients showed deficits in recalling personal episodic memories and facts dating to three different life periods. These deficits were independent of patients' lower verbal memory performance. Additional research is required to gain a better understanding of the pattern and the mechanisms underlying AM impairment in BD.